Pengaruh Profitabilitas dan Ukuran Perusahaan Terhadap Perataan Laba Dengan Kebijakan Dividen Sebagai Variabel Intervening (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2017-2022) - Diega Mergiatma, Egi (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
This research aims to determine the effect of profitability and company size on income smoothing with dividend policy as an intervening variable in manufacturing companies listed on the BEI in 2017-2022. The population of this research includes 98 manufacturing companies listed on the Indonesia Stock Exchange (BEI). The sampling method used was a purposive sampling method, so that 40 sample companies were obtained with a total sample of 240 data for 6 years downloaded from the Indonesia Stock Exchange website. The data analysis methods used in this research are descriptive analysis, classical assumption test, hypothesis test, determinant coefficient test, and path analysis test. Based on the results of data processing using IBM SPSS Statistics Software, the results obtained from this research are: 1) profitability and company size have no effect on income smoothing. 2) profitability has no effect on dividend policy. 3) company size influences dividend policy. 4) dividend policy influences income smoothing. 5) Profitability, company size and dividend policy simultaneously have a positive effect on income smoothing.